THE HISTORY AND TYPES OF HORSE RACES IN THE PLAY CULTURE OF THE KYRGYZ PEOPLE - Ilebayev, Arstanbek (Oriental Journal of History, Politics and Law, 2025)
The article examines another aspect of the Kyrgyz gaming culture related to unproductive activities, all kinds of horse racing. It is known that children were taught to ride horses from an early age. Age–related initiations in the form of atka mingizuu were associated with this. At major horse races, the jockeys were children 7-8 years old, for a light horse race. Sayapkers, experts and specialists in horse preparation for various competitions played a special role. According to sources and field work, more than 14 types of horse racing have been identified so far. Age and gender – aigyr chabysh (horse racing on stallions), Baytal chabysh (horse racing on mares). Tai chabysh (two-year-old horse racing), kunan chabysh (three-year-old horse racing), byshty chabysh (four-year-old horse racing) and at chabysh (adult horse racing). Horse racing was held during times of small and large celebrations. During funerals and funerals. The story describes the kemege baige horse race (on the day of the funeral of the deceased), uchuluk (horse race on the third day of the funeral), zhetilik (horse race on the seventh day of the funeral), kyrk (horse race on the fortieth day of the funeral). Horse racing on the anniversary of death was especially highlighted. It should be noted that the Zhorgo Salysh horse races (pacing) were especially appreciated in the nomadic culture. In its development, horse racing has acquired the status of a national sport.